Cryptic von Hippel-Lindau disease: germline mutations in patients with haemangioblastoma only. Issue 12 (1st December 2000) - Hes, F J; McKee, S; Taphoorn, M J B; Rehal, P; van der Luijt, R B; McMahon, R; van der Smagt, J J; Dow, D; Zewald, R A; Whittaker, J; Lips, C J M; MacDonald, F; et al.
Abstract : OBJECTIVES: Central nervous system haemangioblastoma (HAB) is a major feature of von Hippel-Lindau (VHL) disease, and it is estimated that about 30% of HAB patients have VHL disease. Consequently, it is widely recommended that sporadic HAB patients are screened for clinical and radiological features of VHL disease because of the risk of multiple tumours. We investigated the frequency of VHL germline mutations in patients with HAB only with no clinical or radiological evidence of VHL disease to define the role of molecular genetic analysis in the management of such patients. METHODS: Eighty four patients with a single HAB (23 Dutch, 61 UK) and four with multiple HAB (two Dutch, two UK) were studied by direct sequencing of the coding region and quantitative Southern blotting. RESULTS: A VHL germline mutation was found in three of 69 (4.3%) single HAB patients aged 50 years or less (three of 84 (3.6%) total single HAB patients). A germline VHL mutation was detected in a 44 year old woman with a solitary cerebellar HAB, as well as in four clinically unaffected close relatives, and in two single HAB cases presenting at the ages of 29 and 36 years. Germline VHL mutations were detected in two of four cases with multiple HAB. CONCLUSIONS: Early detection of VHL disease is important to reduce morbidity and mortality and therefore we recommend that, in addition to conventional clinical and radiological investigations, VHL gene mutation analysis should be offered to all HAB patients younger than 50 years. HAB patients aged >50 years will have a lower a priori risk of VHL disease and further data are required to evaluate the role of routine molecular genetic investigations in late onset HAB cases. The failure to detect germline VHL mutations in some patients with multiple HAB may indicate the presence of somatic mosaicism or additional HAB susceptibility genes.